RICHTER'S HERNIA PRESENTING AS FAECAL FISTULA IN FEMALE; A RARE ENTITY - Zia, Muhammad Khurram; Anwar, Hafsa; Naz, Sahira; Wase, Hafiz Abdul; Usmani, Muhammad Saad; Nafees, Taha (Journal of Ayub Medical College Abbottabad, 2017)
Strangulated hernia in quite common in surgical practice and always present with its typical symptoms. In this hardly found unique case, a 76-year's old female with no co morbid presented to us with abdominal pain, vomiting and diarrhoea initially and later developed left groin abscess after 4 days of swelling. It was assumed to be inguinal lymphadenitis leading to abscess formation but after complete evaluation on digital examination, diagnosis of Strangulated Femoral hernia of Richter type was made. This distinguishing presentation among the list of all hernias has to be discussed for the differential diagnosis. Keywords: Richter's hernia; Fecal fistula; Hernia